Increased Hospital and Emergency Department Utilization by Individuals with Recent Criminal Justice Involvement: Results of a National Survey - Frank, Joseph W. (Springer US, 2014)
BACKGROUND: Individuals involved with the criminal justice system have increased health needs and poor access to primary care. OBJECTIVE: To examine hospital and emergency department (ED) utilization and related costs by individuals with recent criminal justice involvement. DESIGN: Cross-sectional survey. PARTICIPANTS: Non-institutionalized, civilian U.S. adult participants (n = 154,356) of the National Survey on Drug Use and Health (2008–2011). MAIN MEASURES: Estimated proportion of adults who reported past year 1) hospitalization or 2) ED utilization according to past year criminal justice involvement, defined as 1) parole or probation, 2) arrest without subsequent correctional supervision, or 3) no criminal justice involvement; estimated annual expenditures using unlinked data from the Medical Expenditure Panel Survey. KEY RESULTS: An estimated 5.7 million adults reported parole or probation and an additional 3.9 million adults reported an arrest in the past year. Adults with recent parole or probation and those with a recent arrest, compared with the general population, had higher rates of hospitalization (12.3 %, 14.3 %, 10.5 %; P < 0.001) and higher rates of ED utilization (39.3 %, 47.2 %, 26.9 %; P < 0.001). Recent parole or probation was an independent predictor of hospitalization (adjusted odds ratio [AOR], 1.21; 95 % confidence interval [CI], 1.02–1.44) and ED utilization (AOR, 1.35; 95 % CI, 1.12–1.63); Recent arrest was an independent predictor of hospitalization (AOR, 1.26; 95 % CI, 1.08–1.47) and ED utilization (AOR, 1.81; 95 % CI, 1.53–2.15). Individuals with recent criminal justice involvement make up 4.2 % of the U.S. adult population, yet account for an estimated 7.2 % of hospital expenditures and 8.5 % of ED expenditures. CONCLUSIONS: Recent criminal justice involvement is associated with increased hospital and ED utilization and costs. The criminal justice system may offer an important point of contact for efforts to improve the healthcare utilization patterns of a large and vulnerable population.